1986
DOI: 10.1007/bf00027131
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequence organization in the genomes of three related millet plant species

Abstract: A major portion of the genomes of three millet species, namely, barn yard millet, fox tail millet and little millet has been shown to consist of interspersed repeat and single copy DNA sequences. The interspersed repetitive DNA sequences are both short (0.15-1.0 kilo base pairs, 62-64% and long (>1.5 kilo base pairs, 36-38%) in barn yard millet and little millet while in fox tail millet, only long interspersed repeats (>1.5 kilo base pairs) are present. The length of the interspersed single copy DNA sequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Molecular genetics. DNA of foxtail millet has several distinguishing features: low nuclear DNA content (haploid, Cvalue, 1C:0.82 pg), low proportion of repetitive DNA (30%), and the presence of a high-melting point component (4.7 to 6.7% of the genome) (Lakshmi and Ranjekar 1984;Siva Raman et al 1986). The total proportion of repetitive DNA was the lowest value in the Poaceae family at the time it was reported (Lakshmi and Ranjekar 1984).…”
Section: Geneticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular genetics. DNA of foxtail millet has several distinguishing features: low nuclear DNA content (haploid, Cvalue, 1C:0.82 pg), low proportion of repetitive DNA (30%), and the presence of a high-melting point component (4.7 to 6.7% of the genome) (Lakshmi and Ranjekar 1984;Siva Raman et al 1986). The total proportion of repetitive DNA was the lowest value in the Poaceae family at the time it was reported (Lakshmi and Ranjekar 1984).…”
Section: Geneticsmentioning
confidence: 99%
“…It has been suggested that this high thermal stability in foxtail millet may indicate very little to no base sequence mismatch, a rare observation, or that this stability maintains internal homogeneity by ''crossover'' fixation (Smith 1976). A major part of the foxtail millet genome (85%) consists only of long interspersed repeated DNA sequences (greater than 1.5 kb; Siva Raman et al 1986). These long sequences can maintain genome size by slow rates of turnover, in which repeated DNA sequences are not subjected to mutations, deletions, or base substitutions at a very rapid rate (Flavell 1980;Siva Raman et al 1986).…”
Section: Geneticsmentioning
confidence: 99%
See 1 more Smart Citation